ANALISIS SIKAP DAN PERILAKU KONSUMEN TERHADAP PEMILIHAN RUMAH TINGGAL PADA KAWASAN SUNSET GARDEN DI KOTA DENPASAR, BALI - Ade Siswanta, I K.; Sudarsana, I K.; Ketut Sudipta, I Gst. (JURNAL SPEKTRAN; vol 2, No 1, Januari 2014, 2014)
The research is motivated by the more selective consumers in choosing a house which impact on changes in market conditions ongoing. Developers should anticipate factors that influence changes in market conditions, such as attitudes and behaviors of consumers in choosing a house. One excample of this condition is development of Sunset Garden area located at Jalan Pura Mertasari Sunset Road, Denpasar, Bali which is this properties are able to attract consumers to buy houses in this area although this price of the house is quite expensive. Therefore, the research was conducted to determine factors that are considered in the selection of residential, consumer attitudes and behavior on the selection of a house and the relationship of consumer characteristics and attributes of products offered in this area. This study used research instruments such as questionnaires to obtain information on the characteristics of respondents and the four components of the attitudes and behavior of the level of confidence, the level of evaluation, the level of normative beliefs and motivation levels. The data analysis technique used is a factor analysis to identify the factors considered in choosing a house, attitudes and behavior analysis with Fishbein method and contingency coefficient analysis to determine the magnitude of the relationship variable product attributes and consumer characteristics. The results of this study indicate the factors that affect the house is 5 (five) factors, they are the location and the legality factors, supporting facilities factors, physical factors, factor values, and environmental factors. Attitudes and behavior are shown in choosing a house on Sunset Garden Zone fall into this category good enough. The results showed that there is a relationship between consumer characteristics and attributes of the product which the consumer's income level has the strongest ties to the variable price of the product.
Keywords: attitude, behavior, fisbein methode, factor analysis, Chi squared analysis, contingency coefficient analysis